1985
DOI: 10.1038/318635a0
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure and expression of a functional human glucocorticoid receptor cDNA

Abstract: Identification of complementary DNAs encoding the human glucocorticoid receptor predicts two protein forms, of 777 (alpha) and 742 (beta) amino acids, which differ at their carboxy termini. The proteins contain a cysteine/lysine/arginine-rich region which may define the DNA-binding domain. Pure radiolabelled glucocorticoid receptor, synthesized in vitro, is immunoreactive and possesses intrinsic steroid-binding activity characteristic of the native glucocorticoid receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
726
0
18

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,740 publications
(751 citation statements)
references
References 63 publications
7
726
0
18
Order By: Relevance
“…Excluding occasional sequence alterations introduced by the Taq polymerase, two types of clones could be distinguished ( Figure 1). One of these clones corresponded to the human GR wild-type sequence, 24 differing only in a known silent polymorphism in codon 766 (AAT-AAC), 25 the other differed by a missense mutation in codon 477 (CGC-CAC), leading to an arginine (R)-histidine (H) exchange. To verify the presence of this productive mutation, we amplified genomic DNA encompassing exon 4 and subjected it to bulk sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…Excluding occasional sequence alterations introduced by the Taq polymerase, two types of clones could be distinguished ( Figure 1). One of these clones corresponded to the human GR wild-type sequence, 24 differing only in a known silent polymorphism in codon 766 (AAT-AAC), 25 the other differed by a missense mutation in codon 477 (CGC-CAC), leading to an arginine (R)-histidine (H) exchange. To verify the presence of this productive mutation, we amplified genomic DNA encompassing exon 4 and subjected it to bulk sequencing.…”
Section: Resultsmentioning
confidence: 99%
“…The specific function of these two mRNAs has not yet been determined but some preliminary observations indicate that they both code for estrogen receptors: their stimulation by estradiol is parallel, they both hybridize, in stringent conditions, with probes containing DNA or hormone binding domains (data not shown). In other species, the presence of multiple steroid receptor mRNA has also been described: in Xen0pu.s four ER mRNAs from 2.5 to 9 kb (Weiler et al, 1987) in rat and man respectively two and three glucocorticoid receptor mRNAs from 4.8 to 7.1 kb (Hollenberg et al, 1985;Miesfeld et al, 1986). Progesterone receptor mRNA seems to be the more heterogeneous with Male rainbow trout (600-900 g) were injected with E, (1.5 mg/kg).…”
Section: Discussionmentioning
confidence: 98%
“…However, recent works show that two forms of human progesterone receptor (hPR), differing in their N-terminal region and proceeding from two classes of hPR mRNAs, exhibit different functional properties (Kastner et al, 1990). Cloning of several steroid receptor's genes reveals that these mRNAs are likely to be transcribed from a unique gene (Huckaby et al, 1987;Ponglikitmongkol et al, 1988;Kuiper et al, 1989) and they might result from the use of different transcription initiation sites (Kastner et al, 1990) or of different polyadenylation sites (Hollenberg et al, 1985). They can also arise from a differential splicing of the same primary transcript (Mitsuhashi et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of glucocorticoids are mediated through the GRa isoform (27) that resides in the cytoplasm in absence of hormone. Several investigations have shown that reductions in the number of GRa molecules/cell result in a decrease in glucocorticoid sensitivity (9 -11, 38, 39).…”
Section: Discussionmentioning
confidence: 99%